2017
DOI: 10.1021/acs.jpclett.7b01357
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Coherent Optical Phonon in 2D Electronic Spectra of CH3NH3PbI3 Perovskite as a Possible Cooling Bottleneck

Abstract: A hot phonon bottleneck may be responsible for slow hot carrier cooling in methylammonium lead iodide hybrid perovskite, creating the potential for more efficient hot carrier photovoltaics. In room-temperature 2D electronic spectra near the band edge, we observe amplitude oscillations due to a remarkably long lived 0.9 THz coherent phonon population at room temperature. This phonon (or set of phonons) is assigned to angular distortions of the Pb-I lattice, not coupled to cation rotations. The strong coupling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 33 publications
12
94
0
Order By: Relevance
“…A comparison of experimental results with computational analysis suggests that large polaron formation results predominantly from coupling between charge carriers and the PbBr 3 − lattice phonons, particularly, the PbBrPb bending modes. Similar conclusions have been reached for polaron formation in MAPbI 3 in measurements based on coherent phonons observed in 2D electronic spectroscopy and THz pump–optical probe spectroscopy, and in ultrafast electron diffraction . The PbBrPb bending modes are coupled to cation motions; as a result, the PbBrPb bending frequencies in CsPbBr 3 are lower than those in MAPbBr 3 .…”
Section: Slow Hot Carrier Cooling In Lhps At ρ ≤ ρMottsupporting
confidence: 79%
“…A comparison of experimental results with computational analysis suggests that large polaron formation results predominantly from coupling between charge carriers and the PbBr 3 − lattice phonons, particularly, the PbBrPb bending modes. Similar conclusions have been reached for polaron formation in MAPbI 3 in measurements based on coherent phonons observed in 2D electronic spectroscopy and THz pump–optical probe spectroscopy, and in ultrafast electron diffraction . The PbBrPb bending modes are coupled to cation motions; as a result, the PbBrPb bending frequencies in CsPbBr 3 are lower than those in MAPbBr 3 .…”
Section: Slow Hot Carrier Cooling In Lhps At ρ ≤ ρMottsupporting
confidence: 79%
“…We note that Price et al reported that for transient absorption measurement, the same feature vanishes with reduced excess energy and might, therefore, also be related to cooling of carriers . Monahan et al observed a rise time of ≈300 fs and a long‐living coherent transverse optical (TO)‐phonon population in 2D electronic spectroscopy . Although the formation of the polaron is associated with the higher frequency LO phonon, coherent (and virtual) phonons, which appear on a shorter timescale than their inverse frequency were reported to accompany the dressing of charge with phonons to form a polaron .…”
Section: Average Cooling Rates Obtained From the Temperature‐ And Excmentioning
confidence: 75%
“…The rise in the photoconductivity is not limited by the generation of free carriers, which has been reported to occur on sub‐100 fs timescales. Rather, it is limited only by the rapid thermalization of carriers …”
Section: Average Cooling Rates Obtained From the Temperature‐ And Excmentioning
confidence: 99%
“…Finally, we show that the emitted THz transients enable a sensitive real‐time probe for carrier–lattice coupling in the hybrid perovskites. Previously, carrier‐induced lattice distortions have been claimed to underpin the efficient hot‐carrier transport, high defect tolerance, and long carrier lifetimes in these materials . In Figure a,d, we first show the amplitude spectrum of the emitted THz fields for 400 and 770 nm excitations, respectively.…”
mentioning
confidence: 99%